Thar Madhu: a new mahua variety - Singh, Sanjay; Singh, A K; Apparao, V V; Bhargava, R (Indian Horticulture, 2019)
The mahua variety-Thar Madhu was identified by Central Institute for Arid Horticulture, Bikaner during the year 2016. The selection outperformed in respect of flowering, fruiting and fruit quality attributes. The tree height and rootstock girth was recorded 4.42 m and 72.21 cm, respectively. North-South and East-West spread was found to be 3.45 m and 3.67 m, respectively. It is spreading type, regular bearer and starts flowering in 5th year. Peak period of flowering is 3rd week of March and it ripens in the month of May. Fresh flowers recorded 26.63o Brix TSS, 1.03% acidity, 23.11% total sugar and 58.61 mg/100g vitamin C. Dry flower yield was recorded 6.32 kg/plant. The variety recorded 29.00 g average fruit weight, 41.74% pulp, 14.26o Brix TSS, 0.10% acidity, 10.80% total sugar and 48.38 mg/100g vitamin C. Fruit yield was recorded 20.14 kg per plant during 10th year of orchard life under rainfed conditions of hot semi-arid ecosystem.